Aramid Nanofiber/MXene-Reinforced Polyelectrolyte Hydrogels for Absorption-Dominated Electromagnetic Interference Shielding and Wearable Sensing - Guo, Jinglun; Zhang, Tianyi; Hao, Xiaoyu; Liu, Shuaijie; Zou, Yuxin; Li, Jinjin; Wu, Wei; Chen, Liming; Liu, Xuqing (Nano-Micro Letters, 2025)
Conductive hydrogels have garnered widespread attention as a versatile class of flexible electronics. Despite considerable advancements, current methodologies struggle to reconcile the fundamental trade-off between high conductivity and effective absorption-dominated electromagnetic interference (EMI) shielding, as dictated by classical impedance matching theory. This study addresses these limitations by introducing a novel synthesis of aramid nanofiber/MXene-reinforced polyelectrolyte hydrogels. Leveraging the unique properties of polyelectrolytes, this innovative approach enhances ionic conductivity and exploits the hydration effect of hydrophilic polar groups to induce the formation of intermediate water. This critical innovation facilitates polarization relaxation and rearrangement in response to electromagnetic fields, thereby significantly enhancing the EMI shielding effectiveness of hydrogels. The electromagnetic wave attenuation capacity of these hydrogels was thoroughly evaluated across both X-band and terahertz band frequencies, with further investigation into the impact of varying water content states—hydrated, dried, and frozen—on their electromagnetic properties. Moreover, the hydrogels exhibited promising capabilities beyond mere EMI shielding; they also served effectively as strain sensors for monitoring human motions, indicating their potential applicability in wearable electronics. This work provides a new approach to designing multifunctional hydrogels, advancing the integration of flexible, multifunctional materials in modern electronics, with potential applications in both EMI shielding and wearable technology. Highlights: 1 Aramid nanofiber/MXene-reinforced polyelectrolyte hydrogels were designed to achieve absorption-dominated electromagnetic interference shielding under the premise of relatively high conductivity. 2 The multifunctional composite hydrogels exhibited outstanding mechanical performance, exceptional adhesion strength, excellent electromagnetic interference shielding and reliable capability for monitoring human motion signals.